Intracranial hemorrhage as presentation of severe hemorragic sindrome by sistemic lonomisms. - Ruiz-Gonzáles, Marie (2020)
The accidents caused by the larval stages of the Lepidoptera are known as erucism. Accidental contact with caterpillars of the genus Lonomia spp. can trigger hemorrhagic syndromes that in severe cases can lead to acute renal injury and intracranial hemorrhage. We present the case of a 48 year-old male from Peruvian Central Jungle who while was working in the forest comes in contact with a caterpillar, after which he developed an hemorrhagic syndrome characterized by coagulopathy and subarachnoid hemorrhage. The clinical picture resolved satisfactorily after administration of antilonomic serum. The pathophysiological, clinical and laboratory aspects that led to the diagnosis are discussed, as well as the reported effectiveness of treatment.